1190 High temperature insulation wools: study of cytotoxic, genotoxic/oxidative and inflammatory effects of polycrystalline wools compared with refractory ceramic fibres. (24th April 2018) - Cavallo, D; Ursini, CL; Campopiano, A; Fresegna, AM; Ciervo, A; Maiello, R; Cannizzaro, A; Angelosanto, F; Iavicoli, S
Abstract : Introduction: Refractory ceramic fibres (RCF) and polycrystalline wools (PCW) constitute a family of fibres known as High Temperature Insulation Wools used in industrial applications above 800°C. Current European Classification, Labelling and Packaging of substances and mixtures classifies RCF as Category 1B ('Substances presumed to have carcinogenic potential for humans'). Regarding PCW toxicity, no studies are available. We aimed to evaluate and compare cytotoxic, genotoxic-oxidative and inflammatory effects of alumina-silicate RCF and PCW on human alveolar (A549) cells. Methods: SEM analysis was performed to characterise fibre dimensions. We exposed for 24 hour the cells to five different concentrations (2–100 µg/ml) of tested fibres to evaluate viability reduction by MTT and Trypan blue assays, membrane damage by LDH release, direct/oxidative DNA damage by Fpg comet assay and IL-6, IL-8 and TNFα cytokine release by ELISA. Results: SEM analysis found a length-weighted geometric mean fibre diameter (D LG ) of 2.1 µm with 68% of respirable fibres for RCF and a D LG of 4.2 µm and 20% of respirable fibres for PCW. Moreover the content of fibres with d<3 µm and l>20 µm was 44% in RCF and 11% in PCW. We found lack of viability reduction for both fibres and membrane damage induction only for RCF at 100 µg/ml. Both the fibres induced dose-dependent DNA damage that, however, was higher for RCF reaching 5.7 fold of control vs 3.8 of PCW. Oxidative effects were induced only by RCF at the lowest concentrations. Regarding inflammatory effects, both the fibres induced only slight increase of IL-6 release at 100 µg/ml. Conclusion: The study confirms the genotoxic/oxidative potential of RCF with thinner D LG, higher percentage of respirable and longer fibres than PCW and shows genotoxicity also for PCW, suggesting also for this fibre with similar chemical composition and low biosolubility, the need of further studies to confirm such results also on other cells.